A study on the relationship between the social-emotional adaptation and behavioral problems of 60-72 month old preschoolers - ÜNSAL, FATMA ÖZGE; RAMAZAN, MÜSLİMAT OYA (ELSEVIER SCIENCE BV, 2012)
The aim of this rearch is to define the relation between social-emotional adaptation and behavior problems of 60-72 month old children. The data collection instruments 'Preschool Behaviour Problem's Scanning Scale' and 'Marmara Social-Emotional Adaptation Scale for 60-72 Month Old Children' were applied to 432 children who were attending public and private preschools in Istanbul. A statistically meaningful and negative relation was found between children's total score of Preschool Behaviour Problem's Scanning Scale and Marmara Social-Emotional Adaptation Scale for 60-72 Month Old Children. As a function of decrease of children's social-emotional adaptation level, their behavior problems increase.
Keywords: social-emotional adaptation; behavioral problems; 60-72 month old preschoolers; SCHOOL